A Modelling Study of Indoor Air Chemistry: The Surface Interactions of Ozone and Hydrogen Peroxide. (15th March 2023) - Carter, Toby J.; Poppendieck, Dustin G.; Shaw, David; Carslaw, Nicola
Abstract: Indoor surfaces play a key role in indoor chemistry, including modification of indoor oxidant concentrations. This study utilises the INdoor CHEmical Model in Python (INCHEM-Py) to investigate the impact of surface transformations and their impact on indoor gas-phase chemistry. INCHEM-Py has been developed to simulate the surface deposition of ozone and hydrogen peroxide onto nine and six individual surfaces respectively in a typical bedroom, kitchen and office for normal indoor concentrations in the absence of household activities. The results show that 91 to 96% of these oxidants are deposited onto indoor surfaces under our simulated conditions. In the bedroom, 38 to 44% of indoor ozone and hydrogen peroxide is deposited onto soft fabric surfaces, with 41 to 54% of ozone deposition occurring on plastic surfaces in the kitchen and office. Total indoor concentrations of straight-chained aldehydes (C1 -C10 ) ranged from ≈ 4 to 5 ppb, with nonanal having the highest individual concentration (1.7, 1.6 and 1.5 ppb in the bedroom, kitchen and office respectively), primarily as a result of emissions from plastics following ozone deposition. Aldehyde concentrations following hydrogen peroxide deposition were often less than 0.01 ppb. Understanding how reactions and deposition on different indoor surfaces impact indoor air chemistry will enable internal surface selection with a view to improving overall indoor air quality. Highlights: Over 90% of indoor O3 and H2 O2 deposits onto indoor surfaces. Bedroom environments remove more O3 and H2 O2 than kitchens and offices. Deposition of O3 increases indoor aldehyde concentrations. Surface reactivity should be accounted for when designing indoor air studies.